Pengaruh Lama Penyimpanan Telur Tetas Pada Suhu Ruang Terhadap Performa Tetas Telur Itik (Anas domesticus) - Haris Nurhaibar Hidayatulloh; Dini Widianingrum; Ulfa Indah Laela Rahmah (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2026)
This study aims to determine the effect of storage time for hatching eggs at room temperature on the hatching performance of duck eggs. This study used a completely randomized design (CRD) with four treatments: P0 (1 day of storage), P1 (3 days of storage), P2 (5 days of storage), and P3 (7 days of storage). Observed variables included fertility, hatchability, and mortality. The results showed that storage time significantly affected the fertility of duck hatching eggs. Storage for one day (P0) produced the best performance with a fertility of 73.34%, a hatchability of 90%, and the lowest mortality of 10%. Meanwhile, storage for seven days (P3) produced the lowest performance. It was concluded that the optimal storage time for duck hatching eggs at room temperature is no more than one day to achieve maximum hatching results.